Mechanical Vibrations Modeling and Measurement - Schmitz, Tony L.; Smith, K. Scott; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Mechanical Vibrations:Modeling and Measurement describes essential concepts in vibration analysis of mechanical systems. It incorporates the required mathematics, experimental techniques, fundamentals of modal analysis, and beam theory into a unified framework that is written to be accessible to undergraduate students,researchers, and practicing engineers. To unify the various concepts, a single experimental platform is used throughout the text to provide experimental data and evaluation. Engineering drawings for the platform are included in an appendix. Additionally, MATLAB programming solutions are integrated into the content throughout the text. This book also: Discusses model development using frequency response function measurements Presents a clear connection between continuous beam models and finite degree of freedom models Includes MATLAB code to support numerical examples that are integrated into the text narrative Uses mathematics to support vibrations theory and emphasizes the practical significance of the results. Mechanical Vibrations:Modeling and Measurement is an ideal book for undergraduate students, researchers, and practicing engineers alike who are interested in developing a more thorough understanding of essential concepts in vibration analysis of mechanical systems.
Introduction -- Single degree of freedom free vibration -- Single degree of freedom forced vibration -- Two degree of freedom free vibration -- Two degree of freedom forced vibration -- Model development by modal analysis -- Measurement techniques -- Continuous beam models -- Receptance coupling -- Appendix A: Orthogonality of eigenvectors -- Appendix B: Beam experimental platform.
Keywords: Engineering; Mechanics; Mechanics, Applied; Vibration; Dynamical systems; Dynamics; Engineering; Vibration, Dynamical Systems, Control; Theoretical and Applied Mechanics; Mechanics; Electronic books